Analysis of Chinese Automotive Firms’ Outbound Mergers and Acquisitions - Cui, Xin (2009)
In the background of domestic boom and economic turmoil, Chinese automotive corporations are seeking their opportunities to grow globally. Outbound Mergers and Acquisitions are regarded as one of the most effective method to achieve their internationalisation goals for Chinese automakers. This research paper examines and explores the Chinese automotive corporations' outbound M&As in the perspectives of motives, drivers, benefits and drawbacks for the Chinese automotive manufacturers‘ cross-border M&As through the single case study of Sichuan Tengzhong‘s acquisition of Hummer brand from GM. By analysing the case study, motives and drivers of Chinese automotive companies could be concluded in the country-specific, industry-specific and company-specific level. Chinese economy taking off and government supports account for the country level incentives. While, the industry level motives and drivers indicate the fierce competition in Chinese automotive industry. In the company-specific level, technology sourcing, market quick entrance, brand value and recognition, and the previous M&A knowledge are the main five incentives for Chinese automakers in their outbound M&As. For the benefits, drawbacks and difficulties in the perspective of Chinese automotive manufacturers, benefits are part of those incentives as sophisticated technology, quick market access, and brand value and shift. Drawbacks and difficulties includes the Chinese government role, over valuation and pricing, poor post-transaction management, lack of strategic future plans, and the economic crisis recently. With the research discussions and findings, this dissertation hopes to reveal and increase the level of the reader‘s knowledge of the outbound M&As from Chinese automotive companies.